Evidences of the insurrection of spouses in the jurisprudence of Imami , Hanafi and Iraqi law - Adnan Salman Qasim - Hussain rajbi - Mustafa Zaki Yahya Al-Lami ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The recalcitrance of spouses is considered issue infestation in all societies, because it is social disagreements usually occurs between couples as a result of certain circumstances experienced by couples some of it are related to them as their morals and behaviors. Some are related to external factors, such as work and its governing circumstances on them and with the intervention of other people as families and friends. Islamic law in the legislation of Imami and Hanafi doctrine, and other doctrines the reasons of recalcitrance were diagnosed and treated according to texts of the sharia of Islamic Which obliged the spouses to respect the rights between them, and developed solutions in the event of recalcitrance from them or one of them, according to the Imami , Hanafi doctrine and  Iraqi law according to al sharia  of Islamic. For his part, the legal articles dealing with the issue of recalcitrance between spouses in the Personal Status Act No. 188 of 1969 Year, as well as article 41   of the Penal Code, stipulated that the spouses must not exceed each other by beating and disability as a result of his recalcitrance and encroachment on the other.